Implementation Of Supply Chain Management In Social Media – Based Online Shop Store (Case Study: Emstore) - Ayu Widyastuti Rafisa; Riska Veronika; Siti Aisyah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This article presents the results of research using descriptive qualitative methods on online business actors based on social media, namely Instagram. The purpose of this research is to see how to use social media as a tool for doing business and what obstacles are faced as well as solutions and efforts that have been and or can be done by online business people. Starting from a network that has expanded, how easy it is for us to start a business through the internet that can benefit us as business beginners. The business you do can be promoted through the internet very easily. The results of the study stated that Instagram social media was considered feasible as a medium for selling online with more effective promotions